„Fedon” Mosesa Mendelssohna i jego recepcja w Polsce - Mróz, Tomasz (Człowiek i Społeczeństwo, 2021)
The paper discusses Moses Mendelssohn’s work Phaedo and its Polish translation which was published in 1829 by Jakub Tugendhold. Although this book did not exert impact on Polish philosophy, Tugendhold, the translator, aimed to use Mendelssohn’s biography and his Phaedo as an instructive example for those representatives of Jewish community who wanted to free themselves from isolation and undergo social and economic, though not religious, assimilation into their Polish and Christian surrounding. Moreover, the author briefly compares Plato’s and Mendelssohn’s Phaedos.